PERFORMANCE SHOPPING HEALTH EXPENDITURE OF EDUCATION AND SHOPPING INFRASTRUCTURE OF WELFARE SOCIETY THROUGH ECONOMIC GROWTH IN THE DISTRICT / CITY IN THE PROVINCE MALUKU - Maximiliane Leonora Cornelia Hukom, Ananda Fajri Candra, Susilo, Khusaini Moh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Expenditure performance in health, education, and infrastructure can be used to encourage and improve the welfare of society through economic growth. Economic growth is driven by increased government spending on public services and technology development to achieve better public welfare.The purpose of the study was to analyze (1) the effect of simultaneous and partial health, education and infrastructure spending on people's welfare in districts/cities in Maluku Province, (2) to analyze the economic growth can mediate the relationship between health, education and infrastructure spending on people's welfare in the Maluku Province. This research is a quantitative research usingpath analysis.The study results showed that (1) spending on health and education directly has a significant effect on people's welfare in districts/cities in Maluku Province. In contrast, direct infrastructure spending has an insignificant effect on community welfare in districts/cities in Maluku Province. Therefore, natural economic growth has an insignificant effect on people's welfare in districts/cities in Maluku province. (2) Government spending, namely health and infrastructure spending, indirectly has an insignificant effect on economic growth, while education spending indirectly has a significant influence on economic growth in districts/cities in Maluku province. Thus, health, education, and infrastructure spending indirectly through economic growth have an insignificant effect on social welfare; this shows that the variable economic growth is not an excellentintervening variable for the health, education, and infrastructure spending variable on the welfare of the district/city community in Maluku province.